LITERATUR REVIEW: HUBUNGAN ANTARA DURASI PENGGUNAAN KOMPUTER DENGAN KELELAHAN MATA PADA KARYAWAN - putri, dian primadia; Arisma, Selvia (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
Background: Excessive computer use can lead to eye fatigue or Computer Vision Syndrome (CVS) due to prolonged screen exposure, non-ergonomic viewing distances, and substandard lighting conditions. This condition can reduce comfort and work productivity. Objective: To determine the relationship between computer usage duration, viewing distance, and workspace lighting with eye fatigue among computer users. Methods: A literature review of five national research articles published between 2023–2025, employing a cross-sectional design and analyzing the relationship between ergonomic factors and eye fatigue. Results: Four out of five articles showed a significant association between computer usage duration and eye fatigue (p < 0.05). Viewing distance and lighting were also influential factors, although results varied across studies. Conclusion: Eye fatigue among computer users is closely related to work habits and non-ergonomic environmental conditions.